2019
DOI: 10.5535/arm.2019.43.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Mirabegron Add-On Therapy to Antimuscarinic Agents in Patients With Spinal Cord Injury

Abstract: ObjectiveTo evaluate the long-term efficacy of mirabegron add-on therapy in patients with spinal cord injury (SCI) based on an urodynamic study.MethodsThis retrospective study involved a chart audit of individuals with SCI who underwent two consecutive urodynamic studies between April 1, 2015 and April 1, 2018. After adding 50 mg of mirabegron once a day to the pre-existing antimuscarinic therapy for a period of, at least 6 months, the following variables were analyzed: change in cystometric capacity, change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Early studies suggest that mirabegron is effective and well tolerated in neurological patients [28], however data in patients with TBI is lacking. The combination of an antimuscarinic agent with a b3 agonist appears has been shown to be effective in patients refractory to antimuscarinic agents alone [29].…”
Section: Treatmentmentioning
confidence: 99%
“…Early studies suggest that mirabegron is effective and well tolerated in neurological patients [28], however data in patients with TBI is lacking. The combination of an antimuscarinic agent with a b3 agonist appears has been shown to be effective in patients refractory to antimuscarinic agents alone [29].…”
Section: Treatmentmentioning
confidence: 99%
“…One study in chronic patients with SCI demonstrated that adding mirabegron to traditional antimuscarinic therapy resulted in long-term improvements to bladder capacity and compliance when compared with antimuscarinic therapy alone. 20…”
Section: Managementmentioning
confidence: 99%
“…The use of mirabegron is currently limited in neurogenic bladder patients, as limited evidence exists to support its use in this population [8,31] . It might be considered as an alternative in patients with contraindication to using anticholinergics, or as an add-on treatment to anticholinergics [35,36] . Table 3.…”
Section: Systemic Medications To Treat Neurogenic Detrusor Over-activitymentioning
confidence: 99%